Вопросы устойчивости решений динамической модели оптимального управления предприятием - Григорьева, Е.В.; Солдатов, М.А. (Культура народов Причерноморья, 2014)
Произведено описание и анализ динамической модели формирования годовой
производственной программы предприятия с учетом финансовых требований. С применением методов
имитационного моделирования исследована стохастическая динамическая модель, которая позволяет
оценить устойчивость оптимальных решений, построить вероятностные распределения
результирующих показателей, произвести подстройку параметров и переменных управления
исследуемой системы. Зроблений опис та аналіз динамічної моделі формування річної виробничої програми
підприємства з урахуванням фінансових вимог. Із застосуванням методів імітаційного моделювання
досліджена стохастична динамічна модель, яка дозволяє оцінити стійкість оптимальних рішень,
побудувати імовірнісні розподілу результуючих показників, призвести підстроювання параметрів і
змінних управління досліджуваної системи. The dynamic model of the formation of enterprise annual production program is constructed and
analyzed. With use of optimization techniques an optimal production plan is calculated, the dynamics of output
variables is studied, effect of boundary conditions of the optimal plan is analyzed. The required value of the loan
is determined in order to satisfy the financial constraints. Addition of financial aspects to the original production
model has led to significant changes in the results of production planning. With use of simulation techniques a
series of experiments with stochastic dynamic model are conducted, which allowed to investigate the stability of
optimal solutions for deterministic dynamic model, to identify the laws of distribution of endogenous variables,
to determine the characteristics of the general population estimates of the output variables and confidence
estimates for control variables of the model. The results of stochastic algorithmic modeling allowed to find optimal values for the parameters and variables of the system, such as total profit, confident assessment values
of optimal amount of credit and minimum stock products. It is shown that the results of stochastic modeling with
sufficient adequacy consistent with the results of a deterministic simulation to determine the optimal production
plan. However, the model is sensitive to fluctuations in demand in terms of satisfaction of financial constraints,
which leads to significant changes in the amount of required finance.